Description and provisional taxonomic designation of an unassociated larval stonefly from Linn County, Oregon (Plecoptera: Perlodidae: Isoperla sp. A) - Sandberg, John B. (Illiesia, 2014)
An unassociated female stonefly larva from Marion Creek, near Marion Falls, Linn County, Oregon, is described under a provisional designation and compared with larvae of other western Nearctic Isoperla species. The lacinia is distinct from the known western larval species.
Keywords: entomology; stoneflies; Perlodidae; Plecoptera; Isoperla; lacinial morphology; Oregon